Editorial - Błasiak, Anna; Dybowska, Ewa (Multidisciplinary Journal of School Education, 2025)
We are pleased to present the latest issue of our journal, Family and School: Educational Partnership. As the authors in this volume demonstrate, the themes addressed here are as timely as they are important. Collaboration between parents and schools is closely linked to children’s educational outcomes. Furthermore, in today’s rapidly changing world means that schools and families can fully achieve its aims without structured collaboration and partnership.